A Rare Cause of Severe Hypoglycemia in Intracranial Hemangiopericytoma Associated With Non-Islet Cell Tumor Hypoglycemia - Natnicha Leelaviwat; Nouran Eshak; Poemlarp Mekraksakit; Ana Cordon; Anupa Patel (Annals of Internal Medicine: Clinical Cases)
A 60-year-old man with a history of metastatic intracranial hemangiopericytoma and type 2 diabetes mellitus presented with acute episodes of confusion and dizziness. A magnetic resonance imaging scan of the brain showed progressing calvarial metastasis without intracranial abnormality. He was found to have severe persistent hypoglycemia. The initial hypoglycemia work-up revealed low serum insulin and C-peptide level and negative panel for oral hypoglycemic agents. Further laboratory testing revealed an elevated insulin-like growth factor II (IGF II):IGF-I ratio and low β-hydroxybutyrate, consistent with nonislet cell tumor hypoglycemia. The patient received prednisone and his hypoglycemia improved.